Comparative Gross Morphometrical Study on Lens in Post-Hatch Rhode Island Red and White Leg Horn Breeds of Poultry - Patra, R.; Mandal, A. K.; Das, R. K. (Indian Journal of Veterinary Anatomy, 2015)
A comparative study was undertaken to elucidate the gross morphometrical features of eye lens in posthatch RIR and WLH breeds of poultry. For the present study, six (6) eyes were collected from female birds of each breed at different age groups (12 wks, 16 wks and 20 wks). The lenses were carefully dissected out. The lens appeared as a crystalline, biconvex disc in both breeds. Its posterior surface was comparatively more convex than the anterior surface. The thickness was maximum along the equatorial plane of lens. The diameter, thickness and curvature of front and back surfaces of lens showed gradual increase with age in both the breeds. In an experimental age group, greater values for the above mentioned parameters were found in WLH breeds as compared to RIR breeds.